A SYNOPSIS OF CALAMUS (ARECACEAE) IN SULAWESI - HIMMAH RUSTIAMI; Andrew Henderson (BRIN Publishing (Penerbit BRIN), 2017)
RUSTIAMI, H. & HENDERSON, A. 2017. A synopsis of Calamus (Arecaceae) in Sulawesi. Reinwardtia 16 (2): 49-63. - A synopsis of the rattan genus Calamus in the Indonesian island of Sulawesi is given. Twenty-three species are recognized, including two new species that are described and illustrated: Calamus posoanus and C. sandsii. Nomenclature, including designation of 17 lectotypes, is given for each species, as well as notes on distribution, habitat, vernacular names, specimens examined, uses, and systematics.